Study of Biogas for Power Generation at Pesantren Saung Balong Al-Barokah, Majalengka, West Java - Maulana Arifin; Aep Saepudin; Arifin Santoso (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2011)
Utilization of biogas from cow manure as a fuel alternative for power plants is done through an anaerobic process. A pilot plant with biogas production of 7 m3/day has been installed at Pesantren Saung Balong. Biogas is used for everyday purposes such as cooking and lighting, and used as pure biogas with 2.500 Watt scale generator. Biogas produced with the rate of 0.080 m3/hr. Biogas produced during the measurement (450 minutes) is 0.604 m3. With these data it is predicted that within a day (24 hours) biogas which can be generated is equal to 1.92 m3. Meanwhile, consumption of biogas to the generator with 1.047 W load is 0.019 m3/minutes, the generator will operate for approximately 101.05 minutes or 1.68 hours. Thus electricity that can be saved is 1.759 kWh per day or 52.77 kWh per month and electricity cost that can be saved that is equal to Rp.40.896/month.